Arctic Education in the Future - Määttä, Kaarina; Uusiautti, Satu (Palgrave Macmillan, 2019)
The Arctic region faces many threats but also opportunities due to economic, climate, and (im)migration-related changes that also necessitate new perspectives on education. What are the special features of teaching and learning in the future Arctic contexts? How to organize the education in the Arctic? The article introduces the essence of Arctic pedagogy by introducing its challenges and goals, possibilities and significance. A model of Arctic pedagogy to be applied in northern education is outlined as a five-level action and teaching tool, which is manifested in learning processes, learning environments, teacherhood, educational leadership, and multiprofessionalism. The cornerstones of Arctic pedagogy are adapting, understanding, and analyzing Arctic information in learning processes, student-centered caring teacherhood, wide-ranging networking to support learning, and communalism. The relationship between Arctic information, its implementation through Arctic pedagogy, and the goals of Arctic future skills are discussed.